Agroecological rotation designs reduce dependence on industrial inputs. Issue 9 (26th November 2017) - Boincean, Boris; Francis, Charles
ABSTRACT: We present results from two 7-year cycles from a polyfactor experiment conducted by Selectia Research Institute of Field Crops on chernozem soil of the Balti steppe (Republic of Moldova) with different crop rotations, tillage, and fertilization strategies (1996–2009). Yields of winter wheat, sugar beet, and maize were higher in rotation with perennial legumes/grasses than without these diverse crops. Adding mineral NPK to farmyard manure increased yields in rotation without perennial legumes and grasses. There was no difference between intensive and minimum soil tillage. Increased nutrient cycling by integrating crop/animal enterprises contributes to greater self-sufficiency in nutrients, providing more resiliency in time of climate changes and economic uncertainty.